Protein-Mediated and RNA-Based Origins of Replication of Extrachromosomal Mycobacterial Prophages - Wetzel, Katherine S. (mBio, 2020)
Temperate bacteriophages are common and establish lysogens of their bacterial hosts in which the prophage is stably inherited. It is typical for such prophages to be integrated into the bacterial chromosome, but extrachromosomally replicating prophages have been described also, with the best characterized being the Escherichia coli phage P1 system. Among the large collection of sequenced mycobacteriophages, more than half are temperate or predicted to be temperate, most of which code for a tyrosine or serine integrase that promotes site-specific prophage integration. However, within the large group of 621 cluster A temperate phages, ∼20% lack an integration cassette, which is replaced with a parABS partitioning system. A subset of these phages carry genes coding for a RepA-like protein (RepA phages), which we show here is necessary and sufficient for autonomous extrachromosomal replication. The non-RepA phages appear to replicate using an RNA-based system, as a parABS-proximal region expressing a noncoding RNA is required for replication. Both RepA and non-RepA phage-based plasmids replicate at one or two copies per cell, transform both Mycobacterium smegmatis and Mycobacterium tuberculosis, and are compatible with pAL5000-derived oriM and integration-proficient plasmid vectors. Characterization of these phage-based plasmids offers insights into the variability of lysogenic maintenance systems and provides a large suite of plasmids for actinobacterial genetics that vary in stability, copy number, compatibility, and host range.